Socioeconomic Factors and The Use of Traditional Medicine in East Seram, Maluku - Ritha Tahitu; Elpira Asmin; Christiana Rialine Titaley; Maxwell Landri Vers Malakauseya; Healdatia R. Malawat; Bela M. Wael; Debora Pormes; Gita Rahmadani (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Although modern medicine continues to develop, traditional medicine is still widely used in various parts of Indonesia, including the natural resource-rich Maluku Province. Socioeconomic conditions are thought to influence people’s dependence on traditional healing practices. This study aimed to analyze the relationship between socioeconomic status and the use of traditional medicine in East Seram District (ESD), Maluku Province. A cross-sectional household health survey was conducted in September-December 2023 among 253 respondents aged 18-65 years in eastern Seram Island. A quantitative-descriptive approach was used with structured interviews and multivariate logistic regression analysis. A total of 45.8% of respondents reported using traditional medicine, especially herbal concoctions. Individuals who do not pay for health insurance membership tend to use traditional medicine (aOR=2.87, 95% CI: 1.66-5.00, p<0.001). Similarly, respondents with low educational attainment (aOR=1.71, 95% CI: 1.00–2.92, p= 0.048) were more likely to use traditional medicine. These results suggest the importance of socioeconomic factors in the use of traditional medicine. Health promotion strategies need to be adapted to the local and cultural context to encourage rational and safe utilization of traditional medicine.